VD_FINDINFO Arrêt / 2011 / 76 vom 16. Dezember 2010 - VD Tribunal cantonal (2010)
PRIVATION DE LIBERTÉ À DES FINS D'ASSISTANCE, TUTELLE, PROVISOIRE, REJET DE LA DEMANDE | 386 al. 2 CC, 397a CC, 380a CPC, 380b CPC, 398a CPC, 398d CPC, 489 CPC, 59 LSP, 70 LSP